Character Analysis of ‘Mathilde Loisel’ in the Maupassant’s “The Necklace” - Yadav, Shubham (International Journal of English Literature and Social Sciences (IJELS), 2019)
The present paper mainly discusses the characterization of Mathilde Loisel in Albert Guy de Maupassant’s “the Necklace” or "The Diamond Necklace”, a short story originally published on February 17, 1884 with an original title: "La Parure". Story takes place in France, during the 1800s, and focuses on the lives of the Loisel family. During that time period, life was hard for the majority of people, who lived primarily in working-class households. Madame Mathilde Loisel, is a round and dynamic character. As a young, married woman, Madame Loisel is pretty and charming, but her vanity makes her feel entitled to more than what she has. In fact, because of her looks, she believes Fate has made a mistake, that she was destined for more. But her dissatisfaction and vanity lead to her downfall, causing her to lose everything she has, including her youth, beauty, and modest way of life, but at the same time, causing her to grow, accept, and respect herself. Essentially by the end of the story, she came to understand her place in life as a very different person.